Nacionalização do trabalho e constituição: análise das regras de nacionalização do trabalho à luz do princípio da isonomia - Vieira Sobrinho, Hamilton (2013)
There is a clear relationship between citizenship and labor market. While foreign nationals are equal in dignity and rights in the laws governing the employment of this labor force. Motivated by reasons of state security or political direction, such laws to a greater or lesser degree, create establish a system of worker protection in the face of the foreign national. These rules have a direct impact on economic regulation, as they can affect the supply of skilled labor or not, articulating with the economic order envisaged by the 1988 Constitution. The Constitution adopts several principles in its economic order, so that the issues involving the rules of the nationalization of all work must be considered in a systematic way, one can not choose a pleasure interpreter. The nationalization of the work rules are not unique to Brazil, similar rules exist in several countries of South America and Africa. In Europe they already existed, but lost out on the basis of treaties setting up the European Union, although other mechanisms are used for the purpose of protecting the citizens of the member states, making policies equal treatment legislation symbolic. The nationalization of the work rules governing the relationship between nationality and the labor market and are in a legal category, which has a function to fulfill in the Brazilian legal system. Not all rules nationalization violate the principle of equality, as it is possible, depending on the circumstance indeed adopt a criterion that implies differentiation between nationals and foreigners. The Constitution has a will arising from its normative force, so that the assumptions it (constitution) used to discriminate may also be possible by ordinary legislation, since the situation is actually justifiably constitutional